2014
DOI: 10.4111/kju.2014.55.3.190
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preoperative Flow Rate on Postoperative Retention and Voiding Difficulty After Transobturator Tape Operation

Abstract: PurposeControversy exists over the preoperative risk factors for postoperative urinary retention after the midurethral sling procedure for stress urinary incontinence (SUI). We intended to analyze the effect of preoperative flow rate on postoperative urinary retention after the transobturator tape (TOT) operation.Materials and MethodsA total of 322 patients who underwent TOT from June 2006 to May 2012 were included in this retrospective study. All patients were preoperatively investigated for urinary symptoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
2

Year Published

2016
2016
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 29 publications
1
9
2
Order By: Relevance
“…In the TOT procedure, postoperative urinary retention had no correlation with preoperative urinary [11]. Two red circles indicate the patients who needed cholinergic agents after the TOT procedure flow rates [18]; however, previous studies demonstrated that preoperative Qmax below 15 mL/s was a predictor for the development of postoperative voiding dysfunction [19,20]. In our present study, none of the patients had postoperative urinary retention.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…In the TOT procedure, postoperative urinary retention had no correlation with preoperative urinary [11]. Two red circles indicate the patients who needed cholinergic agents after the TOT procedure flow rates [18]; however, previous studies demonstrated that preoperative Qmax below 15 mL/s was a predictor for the development of postoperative voiding dysfunction [19,20]. In our present study, none of the patients had postoperative urinary retention.…”
Section: Discussioncontrasting
confidence: 51%
“…Therefore, further examinations to compare age-adjusted cQmax in patients and healthy women will solve the clinical question regarding high urinary flow in SUI patients. A correlation between low urinary flow rate and postoperative voiding dysfunction in MUS has been well discussed in several studies [17][18][19][20]. In the TOT procedure, postoperative urinary retention had no correlation with preoperative urinary [11].…”
Section: Discussionmentioning
confidence: 96%
“…25 Kim et al found that preoperative low Qmax was not associated with postoperative retention and voiding difficulty after TOT operation. 26 In a study of Ingber et al women with severe obstructive LUTS rather had significant improvement in their symptoms after MUS procedure, and there was no subject showing retention or voiding difficulty at follow-up, implying that they can safely managed with MUS procedures. 27 For the treatment of prolonged voiding difficulty after sling procedure, various methods of sling incision have been reported with high success rates.…”
Section: Discussionmentioning
confidence: 95%
“…Kim et al. found that preoperative low Qmax was not associated with postoperative retention and voiding difficulty after TOT operation . In a study of Ingber et al.…”
Section: Discussionmentioning
confidence: 96%
“…For assessment of the mesh tension, cough stress test (CST) is used intreoperatively while TOT procedure (11). As less tension is associated with leaving the patient incontinent, more tension may cause voiding disorders (12). In this study, we evaluated affect of CST on TOT procedure success rate and patients quality of life with using the Incontinence Impact Questionnaire and Urinary Distress Inventory Questionnaire.…”
mentioning
confidence: 99%